Persepsi Masyarakat terhadap Kinerja Pengelolaan Daerah Aliran Sungai Ciliwung: (Studi Kasus Kelurahan Cipinang Muara dan Kelurahan Bukit Duri) - Kresno Agus Hendarto (Jurnal Manajemen Hutan Tropika, 2005)
This study describes the use of correspondence analysis for examining the relationship between perception of the community, residing in Cipinang Muara village and Bukit Duri village, and the performance of Ciliwung watershed management. The correspondence analysis provided a particular method that was able to describe the data in an Euclidean space such that the results could be visually examined for structure of categorical variables included in the tables. The study found that perception of the community residing in Cipinang Muara village significantly differed from that in Bukit Duri village. The attributes that might influence such differences were linked to the institution achievement, and further could be divided into two groups. The first group includes flood, landslide, soil fertility, extra/ additional incomes, and transparent activity; while the second includes drought, spring facility, road facilities and aids, when disaster occurred. The combination of both perception of the community and the performance of Ciliwung watershed management suggests that community in Bukit Duri village had a bad perception on attributes drought, spring facility, road facilities, and aids when disaster occurred. Meanwhile, there was a bad perception for the community in Cipinang Muara village toward attributes flood, landslide, soil fertility, extra/ additional incomes, and transparent activity.